Legal Protection for Girl Victims of Human Trafficking for Prostitution - Yuda, Debila Majesa; Kayus Kayouan L (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
Human trafficking for prostitution is a form of transnational crime that has serious impacts, especially for girls as the most vulnerable group. This study aims to examine the form of legal protection provided to female victims of human trafficking for prostitution, both within the scope of national law and international law. The research method used is normative juridical with a regulatory approach, contextual approach, and case approach. The data used is secondary qualitative data, obtained through a literature review of regulations, legal literature, and court decisions. The results of the study indicate that although normatively there have been various legal instruments that regulate the protection of children from human trafficking practices, implementation in the field still faces a number of challenges, such as weak law enforcement, minimal recovery for victims, and suboptimal relations between institutions. Therefore, it is necessary to strengthen protection policies, increase the capacity of law enforcement officers, and recovery based on victim rights so that legal protection for female victims of human trafficking for prostitution can be realized effectively.